Near-tetraploid T-cell acute lymphoblastic leukaemia in childhood: Results of the AIEOP-BFM ALL studies. (November 2022) - Ceppi, Francesco; Gotti, Giacomo; Möricke, Anja; Silvestri, Daniela; Poyer, Fiona; Lentes, Jana; Bergmann, Anke; Trka, Jan; Alten, Julia; Elitzur, Sara; Barbaric, Draga; Buldini, Barbara; et al.
Abstract: Background: Near-tetraploidy–defined by DNA index 1.79–2.28 or 81–103 chromosomes–is a rare cytogenetic abnormality observed both in children and adults with T-cell acute lymphoblastic leukaemia (T-ALL) and its prognostic value is not yet determined. Patients and methods: We report a retrospective study conducted in paediatric patients with newly diagnosed T-ALL treated in AIEOP-BFM ALL 2000 and 2009 studies. 31 near-tetraploid T-ALL patients (1.4%) are compared to T-ALL patients without near-tetraploidy. Results: Near-tetraploid karyotype was associated with lower frequency of high-risk features: white blood cells count at diagnosis ≥100, 000/μL (19.3% versus 41.0%, p-value < 0.001), PPR (13.3% versus 35.8%, p-value = 0.01) and minimal residual disease high-risk at the end of consolidation phase Induction B (4.03% versus 14.6%, p-value = 0.001). Complete remission was achieved at the end of induction phase (day 33) in 100% near-tetraploid T-ALL patients, compared to 93.2% T-ALL without near-tetraploidy. Conclusion: Overall, we found that near-tetraploid T-ALL in newly diagnosed paediatric patients is associated with low-risk presenting features, with favourable treatment response and outcome. Highlights: T-cell acute lymphoblastic leukaemia (T-ALL) lacks recurrent chromosomal rearrangements with independent prognostic value. Near-tetraploidy is a rare cytogenetic abnormality observed in T-ALL. Near-tetraploid T-ALL is associated with favourable treatment response and outcome.